North Atlantic Ocean decadal variability over the past millennium from climate model simulations and proxy based reconstructions - Pyrina, Maria (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
The present work is focused on the study of North Atlantic (NA) past ocean variability during the last millennium and the potential influence of natural external forcing. The analysis is conducted by using both molluscan-based proxy records and output of state-of-the-art comprehensive Earth System Models. The marine proxy records that are used are the growth increments of the bivalve shell Arctica islandica. The model simulations used participate in the fifth phase of the Climate Model Intercomparison Project (CMIP5). In particular, with this work I seek to answer the following questions: i) Does Arctica islandica have the potential to be used in Climate Field Reconstructions (CFRs) of the sea-surface-temperatures (SSTs) in the NA Ocean? ii) If there is a NA basin signal registered in Arctica islandica locations, which CMIP5 models can reproduce that signal? iii) Which climate reconstruction techniques are the most suited to reconstruct SSTs based on Arctica islandica? iv) Is the climate model or the statistical reconstruction method more important to evaluate the skill of the reconstruction? v) Do changes in solar forcing affect upper ocean circulation during summer? Initially, I investigated the spatial covariance of the SSTs over two Arctica islandica collection sites with the North Atlantic wide SST field, using COBE2 reanalysis data and CMIP5 model output, during the second half of the 20th century. The SSTs co-located with the Arctica islandica collection sites are found to co-vary with the north-east Atlantic basin. Therefore, Arctica islandica has the potential to provide a skillful spatial reconstruction of the SSTs over this area. These results are shown by both COBE2 data and CMIP5 models. Additionally, eleven CMIP5 models were evaluated regarding the possibility to be used as test beds for the assessment of CFR methods that can be applied to reconstruct basin wide SSTs from the collection of proxy records of Arctica islandica. The best performing CMIP5 models in this regard are: CanESM2, CCSM4 and ...